Discrimination of fearful and happy body postures in 8-month-old infants: an event-related potential study - Missana, Manuela; Rajhans, Purva; Atkinson, Anthony P.; Grossmann, Tobias (Frontiers in Human Neuroscience, 2014)
Responding to others’ emotional body expressions is an essential social skill in humans. Adults readily detect emotions from body postures, but it is unclear whether infants are sensitive to emotional body postures. We examined 8-month-old infants’ brain responses to emotional body postures by measuring event-related potentials (ERPs) to happy and fearful bodies. Our results revealed two emotion-sensitive ERP components: body postures evoked an early N290 at occipital electrodes and a later Nc at fronto-central electrodes that were enhanced in response to fearful (relative to happy) expressions. These findings demonstrate that, (a) 8-month-old infants discriminate between static emotional body postures, and (b) similar to infant emotional face perception, the sensitivity to emotional body postures is reflected in early perceptual (N290) and later attentional (Nc) neural processes. This provides evidence for an early developmental emergence of the neural processes involved in the discrimination of emotional body postures.